A Study of the Potential of Ecotourism Development in Konawe Islands Regency, Southeast Sulawesi Province, Indonesia - Hidrawati Hidrawati; Normayasari Normayasari; Sariamin Sahari; Samsul Alam Fyka; Wa Ode Yusria (HABITAT, 2020)
The ecotourism potential development in Konawe Islands, Southeast Sulawesi Province requires academic study as a foothold in region policy making by all development stakeholders. This study aims to provide data and information about the potential of natural resources could be the ecotourism object, analyzing the perceptions of local communities, and formulating strategic plan for ecotourism development. The study was conducted from April-October 2019. This research used quantitative methods with data that were collected from observations, interviews, Focus Group Discussion (FGD) and literature studies. Data analysis was made using quality criteria scale of flora fauna diversity, SWOT analysis and litmus tests. The results of the study showed that Konawe Islands Regency has potential ecotourism objects in coastal-sea panoramas (Sawaea beach and Kampa beach), and in the mainland-hills with waterfalls panoramas (Tumburano waterfalls and Lanuku waterfalls). The results of importance/significance measurements indicate that the flora potential have a scale value of 3 (moderate), the fauna potential have scale of value 4 (good) and the potential criteria of "B", which indicates that the tourist attraction has a potential quality to be developed as ecotourism. Local people's perception is very positive because they believe there are economic, socio-cultural and ecological benefits from ecotourism development. The results of the SWOT analysis with the Litmus test found some main strategies in form program plans such as increasing the knowledge and skills tourism community, increasing the availability of capital financial for ecotourism businesses and development of ecotourism infrastructure facilities. Besides that, the main strategies from SWOT analysis result are promotion of ecotourism objects, the stipulation of rules about management of attractions; and deal with potential conflict issues and abrasion or erosion.